A New Model for Creating Layer Planes Using Steganography for Text Hiding - Mshir, Shalaw; Varol, Asaf (Ieee, 2019)
Steganography is the art and science of hiding messages in a secret way such that only the sender and receiver know. This allows one party to communicate with another without a third party knowing that the connection is taking place. Here, the data is hidden inside a safe cover, where even if a third party can capture the cover, there will be nothing to show what data is hidden inside. Meanwhile, the cover can be an image, sound, video or document. Steganography has two primary aspects: security - whether the hidden data is perceptible by either a person or a computer; and capacity - how much data can be hidden in a given cover file. Because the system works within a spatial domain, it can hide a large amount of information, while embedding and extraction processes require less time in terms of execution than methods using transform domains. This paper explains how to use steganography through a modern technique with a practical understanding.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: information hiding; steganography; image steganography; embedding; extraction